Risk factors and molecular characterization of penile cancer: impact on prognosis and potential targets for systemic therapy. Issue 2 (March 2020) - Thomas, Anita; Vanthoor, Joren; Vos, Gigi; Tsaur, Igor; Albersen, Maarten
Abstract : Purpose of review: To provide a comprehensive summary of risk factors, molecular machinery as well as potential therapeutic targets with a particular focus on literature published in the last 2 years on prognosis and treatment of penile cancer (PeCa). Recent findings: E2F, LAMC2, MAML2, ID1 and IGFBP2 proteins were demonstrated to play a critical role for aggressive tumor behavior and might predict poor survival in PeCa. PD-L1 axis was confirmed as a promising pathway to serve as a therapeutic target. A number of genetic alterations were illuminated. In clinical testing, pan-HER tyrosine kinase inhibitor dacomitinib provided promising results in chemo-naïve and EGFR monoantibody nimotuzumab in chemotherapy-failed PeCa patients. Summary: Knowledge of prognosis-relevant altered molecular pathways in PeCa is expanding paving the way for identification of potential therapeutic targets. Multicenter clinical trials in the setting of centralized PeCa care are warranted to foster effective marker-based individualized treatment strategies.